Uncovering Iranian mothers' perceptions of their bilingual children's home digital literacy practices in English - Soyoof, Ali (Interactive learning environments, 2024)
In Iran, many children spend a great deal of their time in home contexts where they often use different digital technologies such as smartphones, tablets, and some other digital devices. However, the way that children use these digital technologies largely depends on their mothers whose perceptions can shape their home digital literacy practices. While mothers' perceptions of their children's home digital literacy practices have been investigated in other contexts such as Turkey, Spain, England, and Sweden, there is a scarcity of knowledge about the perceptions of Iranian mothers. To bridge this gap, I conducted a qualitative case study using demographic profiles and semi-structured interviews to uncover Iranian mothers' perceptions of their bilingual children's home digital literacy practices in English. Drawing on thematic analysis, the findings demonstrated that while Iranian mothers urged their children to engage in home digital literacy practices in English, they had different motives such as migration, higher education, decision-making, practical skills, and early formal education. The findings of this study can offer valuable insights to the Iranian English language teaching (ELT) stakeholders to better address the needs of Iranian children and their parents using digital technologies in English.